KURIKULUM PENDIDIKAN ISLAM ERA SOCIETY 5.0 BERINTEGRASI DENGAN ANALISIS TEP (TEKNOLOGI, NILAI ETIKA, DAN PEDAGOGI) - Hikmawati, Lila; Fauziyah, Nina Rohmatul; Shoimah, Retno Nuzilatus; Rohanah, Titiek; Saefrudin, Saefrudin (MIDA : Jurnal Pendidikan Dasar Islam, 2026)
The emergence of Society 5.0 requires educational systems to integrate digital technology with humanistic and ethical values, including within Islamic education. However, technology adoption in Islamic institutions often remains instrumental and has not been systematically aligned with moral, spiritual, and pedagogical dimensions. This study aims to examine an integrated Islamic education curriculum model based on the Technology–Ethics–Pedagogy (TEP) framework to address the challenges of Society 5.0. A qualitative approach was employed through literature review and case studies in three Islamic educational institutions in Lamongan. Data were collected through document analysis and semi-structured interviews with fifteen educators, curriculum developers, and policymakers, and analyzed using thematic analysis. The findings reveal that technology integration is still selective and primarily functions as a supporting tool, while Islamic ethical values are emphasized normatively but are not yet fully formalized within the written curriculum. Key challenges include cultural resistance, limited digital infrastructure, and unequal teacher competencies. Nevertheless, several local innovations demonstrate contextual practices that combine digital literacy with Islamic moral and spiritual principles. The study concludes that effective curriculum transformation depends not solely on technological sophistication but on a balanced integration of technology, ethics, and pedagogy to foster digitally literate and ethically grounded Muslim learners.